Malicious intent - Blackburn, Lynn Huggins (Blackburn, Lynn Huggins. Defend and protect, 2022)
"Driven by a traumatic event in her past, Dr. Ivy Collins is on the precipice of a scientific breakthrough after years of research and sleepless nights when dangerous circumstances demand that she give it all up-to save someone else. Can US Secret Service Agent Gil Dixon work with her to help save her work-and her life?"--